Palynology of the genera Tarasa and Wissadula (Malvaceae, Malveae) from Argentina - Graciela A. Cuadrado; Angel R. Miño Boilini (Bonplandia, 2006)
Pollen grains of twenty one species of two genera of Malvaceae were studied and described under optical and scanning microscopy; Tarasa Phil.: T. alberti Phil., T. antofagastana (Phil.) Krapov., T. capitata (Cav.) D. M. Bates, T. heterophylla(Griseb.) Krapov., T. humilis (Gill. ex Hook & Arn.) Krapov., T. meyeri Krapov., T. odonellii Krapov., T. tarapacana (Phil.) Krapov., T. tenella (Cav.) Krapov., T. trisecta(Griseb.) Krapov., T. urbaniana (Ulbr.) Krapov., and Wissadula Medik: W. decora S. Moore, W densiflora R.E.Fr., W. glechomaefolia (A. St.-Hil.) R.E.Fr., W. gymnanthemum (Griseb.) K. Schum., W. paraguariensis Chodat, W. parviflora(A.St.-Hil.) R.E.Fr., W. setifera Krapov., W. subpeltata (Kuntze) R.E.Fr., W. tucumanensis R.E.Fr. and W. wissadifolia (Griseb.) Krapov. They showed differences at generic level, excepting Tarasa alberti which has affinities with theWissadula group. Pollen grains are spheroidal, oblate-spheroidal and suboblate, medium to large sized. The apertures show variations in number (three to eight), but all they are colporate and have different distribution patterns: zonocolporate and spiralloid. The sculpture does not show marked differences on the surface; the most of them are echinate, echinulate with nanospinulae and perforations (foveas) between the spines or spinulae. Two keys to determine the species of each genus and distinguish the three recognized pollen types are given: 1) tri-tetracolporate, 2) pentazonocolporate and 3) oligocolporate (6-8 apertures) spiraloid arrangement.